ESTIMASI PASOKAN BATUBARA UNTUK PLTU RENCANA DI PROVINSI KALIMANTAN BARAT - Sartika Sartika (INOVTEK POLBENG, 2018)
Abstrat - Coal is a cheap of fossil energy and encouraged in the framework of national energy diversification. Based on the Handbook of Energy and Economic Statistics of Indonesia 2016, Indonesia's coal reserves amounted to 32 billion tons which are spread on the islands of Sumatra and Borneo. Most of the domestic coal demands are currently used as fuel for PLTU to produce electricity. Based on the RUPTL PLN, to increase the reliability of the electricity system in West Borneo, the construction of non-fuel power plants such as the Parit Baru Power Plant (FTP1 and FTP2) and the Pantai Kura-Kura PLTU (FTP1). However, in West Borneo coal has not been exploited and coal reserves have also not been identified. To ensure the continuity of electricity supply in West Borneo Province, its need to estimated coal supply for the planned PLTU in West Borneo Province. which require data such as the coal specification data that will be used in the PLTU plan. After the data is collected, then the coal demands are calculated for each planne PLTU.